Field-controlled spin current in frustrated spin chains - Kolezhuk, A.K.; McCulloch, I.P. (Condensed Matter Physics, 2009)
We study states with spontaneous spin current, emerging in frustrated antiferromagnetic spin-S chains subject
to a strong external magnetic field. As a numerical tool, we use a non-Abelian symmetry realization of the
density matrix renormalization group. The field dependence of the order parameter and the critical exponents
are presented for zigzag chains with S = 1/2, 1, 3/2, and 2. Ми дослiджуємо стани зi спонтанним спiновим струмом, який виникає у фрустрованому антиферомагнiтному спiн-S ланцюжку, помiщеному у зовнiшнє магнiтне поле. В якостi чисельного методу ми використовуємо неабелеву реалiзацiю методу ренормалiзацiйної групи для матрицi густини. Представленi польовi залежностi параметра порядку i критичних показникiв для зиґзаґ ланцюжкiв з S = 1/2, 1, 3/2 i 2.